2007
DOI: 10.1080/10408390600754248
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Structures in Bulk Oils on Lipid Oxidation

Abstract: Lipid oxidation is important to food manufacturers especially when they increase unsaturated lipids in their products to improve nutritional profiles. Unfortunately, the number of antioxidants available to food manufacturers to control oxidative rancidity is limited and the approval of new antioxidants is unlikely due to economic barriers in obtaining government approval for new food additives. Therefore, new antioxidant technologies are needed for food oils. This paper reviews the current knowledge of lipid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
411
1
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(441 citation statements)
references
References 101 publications
10
411
1
19
Order By: Relevance
“…Essa diferença pode ter sido resultante dos efeitos dos processos de hidrólise e oxidação lipídica durante o armazenamento, conforme mostrado com o aumento dos índices de acidez e peróxidos. Esse resultado corrobora os obtidos por Chaiyasit et al (2007), que afirmaram que a lipoperoxidação diminui o valor energético do alimento, em decorrência da destruição dos ácidos graxos. Mujahid et al (2003) relataram menores valores de digestibilidade da gordura com o tempo de armazenamento do farelo de arroz; no entanto, a magnitude desse efeito depende do nível de inclusão e do processamento térmico ao qual o farelo foi submetido.…”
Section: Resultsunclassified
“…Essa diferença pode ter sido resultante dos efeitos dos processos de hidrólise e oxidação lipídica durante o armazenamento, conforme mostrado com o aumento dos índices de acidez e peróxidos. Esse resultado corrobora os obtidos por Chaiyasit et al (2007), que afirmaram que a lipoperoxidação diminui o valor energético do alimento, em decorrência da destruição dos ácidos graxos. Mujahid et al (2003) relataram menores valores de digestibilidade da gordura com o tempo de armazenamento do farelo de arroz; no entanto, a magnitude desse efeito depende do nível de inclusão e do processamento térmico ao qual o farelo foi submetido.…”
Section: Resultsunclassified
“…Além de apresentarem bioatividade no organismo humano, os antioxidantes naturais protegem os óleos vegetais contra a ação de radicais livres que iniciam e perpetuam a peroxidação lipídica, que consiste na principal forma de degradação dos óleos vegetais e em importante fonte de prejuízos para a indústria de alimentos 3 . Dessa forma, os antioxidantes naturais presentes nos óleos vegetais têm sido foco de interesse científico e tecnológico nas áreas de ciência de alimentos e nutrição, a partir de duas abordagens principais: promoção de maior estabilidade oxidativa dos óleos e bioatividade no organismo humano.…”
Section: N T R O D U ç ã Ounclassified
“…It was found that polar antioxidants (e.g. ascorbic acid, carnosic acid, and rosmarinic acid) are the most effective in bulk oils, due to their accumulation at the air-oil interface or in reverse micelles within the oil where lipid oxidation reactions occur (Chaiyasit et al, 2007;Heins et al, 2007;McClements and Decker, 2000). The higher efficiency of nonpolar antioxidants in emulsions is a result of their concentration at the interface between the lipid and the polar phase, so that the antioxidant is ideally located to protect the lipids from radicals generated in the aqueous phase.…”
Section: Discussionmentioning
confidence: 99%